Studying the Use of Mortgaged Property from the Perspective of Islamic Sharia and Legal System of Afghanistan (Salam International Academic Journal, 2022)
The mortgage contract is one of the contracts that is very widely used in our society today, and the majority of people are at a crossroads regarding the permissibility and impermissibility of utilizing mortgaged property, and they have many questions that they want to be answered.  In this research, matters related to the mortgage contract, the legitimacy of the mortgage, the elements of the mortgage, the conditions of the mortgage, the types of mortgage, how to use the mortgaged property, the views of the jurists of four major schools of jurisprudence regarding the permissibility and impermissibility of using the mortgaged property are discussed, based on a library method of research. The research ends with a conclusion and a list of references.
Keywords: mortgage contract; mortgage legitimacy; how to use mortgaged property; Islamic Jurisprudence; law